The impact of maternal mental health shocks on child health: Estimates from fixed effects instrumental variables models for two cohorts of Australian children - Nguyen, Ha; Le, H. (Curtin University, 2016)
This paper contributes to an emerging body of literature on intergenerational transmission in health by presenting the causal estimates on the impact of maternal mental health shocks on child health. The potential endogeneity of maternal mental health shocks is dealt with by utilising nationally representative panel data from two cohorts and individual fixed effects instrumental variables models. While our results show that poor maternal mental health does not affect children’s general health, asthma morbidity or anthropometric measures, our results indicate that children of depressed mothers do need extra medical care. For this child health outcome, higher adverse impact is found for boys, younger children, children of mothers with lower education and children in lower income households. We also find that children of depressed mothers are more likely to have food or digestive allergies and tonsillitis incidence. Our study demonstrates that failing to account for endogeneity of maternal mental health shocks could over-estimate the harmful impact of poor maternal mental health on child health. Our findings are robust to a battery of sensitivity and specification tests.